Health culture construction in Shandong province, current situation and countermeasures: a cross-sectional survey - Jin WANG; Ai-wen WANG; Wei LIU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the status and existing problems of healthy culture construction in 20 pilot cities (counties) in Shandong province from 2016 to 2017 for making some suggestions to the construction of healthy cities. Methods We conducted a questionnaire survey to collect relevant information of 2016 - 2017 on health culture construction among the 20 pilot administrative regions in Shandong province. The selection of indicators for the progress of heath culture construction was based on the "Evaluation Index System of National Healthy City - 2018 Version" issued by National Patriotic Health Association. Changes in the indicators and associations between the indicators and economic conditions were analyzed statistically. Results Compared to those in 2016, general improvements in healthy culture construction related indicators were observed in 2017 for the pilot regions, with the health literacy rate significantly increased by 2.3% to 16.1%, the average smoking rate for the residents over 15 years old significantly decreased by 0.9% to 20%, the proportion of the residents taking part in regular physical exercise increased by 2.9% to 32.3%, the average number of health popularization website pages increased by 8.2, the average number of television and radio programmes on health promotion increased by 1.8 and 1.5, the average number of health columns on newspapers increased by 22.4, and the ratio of registered volunteers increased by 3.4%, respectively. In terms of health promotion in the media, there were significant disparities in the number of website pages, television and radio programmes, and newspaper columns among the pilot regions with different gross domestic production (GDP) per capita and the regions with higher GDP had more health promotion programmes in the media. Conclusion The construction of health culture in the pilot regions in Shandong province has achieved remarkable results but efforts should be made in some aspects of the construction; economic development has positive effects on health culture construction in the pilot regions.